Boswellic Acid Improves Cognitive Function in a Rat Model Through Its Antioxidant Activity - Neuroprotective effect of Boswellic acid - - Saeedeh Ebrahimpour; Mehdi Fazeli; Soghra Mehri; Mahnaz Taherianfard; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2017)
Objectives: Boswellic acid (BA), a compound isolated from the gum-resin of Boswellia carterii, is a pentacyclic terpenoid that is active against many inflammatory diseases, including cancer, arthritis, chronic colitis, ulcerative colitis, Crohn's disease, and memory impairment, but the mechanism is poorly understood. This study investigated the effects of boswellic acid on spatial learning and memory impairment induced by trimethyltin (TMT) in Wistar rats. Methods: Forty male Wistar rats were randomly divided into 5 groups: Normal group, TMT-administrated rats (8.0 mg/kg, Intraperitoneally, i.p.) and TMT + BA (40, 80 and 160 mg/kg, i.p.)-administrated rats. BA was used daily for 21 days. To evaluate the cognitive improving of BA, we performed the Morris water maze test. Moreover, to investigate the neuroprotective effect of BA, we determined the acetylcholinesterase (AchE) activity, the malondialdehyde (MDA) level as a marker of lipid peroxidation, and the glutathione (GSH) content in the cerebral cortex. Results: Treatment with TMT impaired learning and memory, and treatment with BA at a dose of 160 mg/kg produced a significant improvement in learning and memory abilities in the water maze tasks. Consistent with behavioral data, the activity of AChE was significantly increased in the TMT-injected rats compared to the control group (P < 0.01) whereas all groups treated with BA presented a more significant inhibitory effect against AChE than the TMT-injected animals. In addition, TMT reduced the GSH content and increased the MDA level in the cerebral cortex as compared to the control group) P < 0.01). On the other hand, treatment with BA at 160 mg/kg slightly increased the GSH content and reduced the MDA level in comparison to the TMT-administered group (P < 0.01). Conclusion: The above results suggest that the effect of BA in improving the cognitive function may be mediated through its antioxidant activity.